2018
DOI: 10.1128/iai.00935-17
|View full text |Cite
|
Sign up to set email alerts
|

The Adjuvant Bordetella Colonization Factor A Attenuates Alum-Induced Th2 Responses and Enhances Bordetella pertussis Clearance from Mouse Lungs

Abstract: The reemergence of pertussis or whooping cough in several countries highlights the need for better vaccines. Acellular pertussis vaccines (aPV) contain alum as the adjuvant and elicit Th2 biased immune responses that are less effective in protecting against infection than the reactogenic whole cell pertussis vaccines (wPV), which elicit primarily a Th1/Th17 response. An important goal for the field is to devise aPVs that will induce immune responses similar to wPV. We show that Bordetella Colonization Factor A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…We previously reported that immunization with BcfA/Alum protected mice against B. bronchiseptica challenge(24). BcfA also enhanced immune responses to heterologous antigens and to Bordetella vaccine antigens FHA and Prn(25). These results suggested a dual protective function of BcfA as an antigen and an adjuvant.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously reported that immunization with BcfA/Alum protected mice against B. bronchiseptica challenge(24). BcfA also enhanced immune responses to heterologous antigens and to Bordetella vaccine antigens FHA and Prn(25). These results suggested a dual protective function of BcfA as an antigen and an adjuvant.…”
Section: Resultsmentioning
confidence: 99%
“…FHA and Prn alone or adjuvanted to alum elicit Th2-skewed antibody responses(25). To determine whether BcfA remodeled these responses towards Th1 we evaluated the systemic and mucosal IgG levels and calculated the ratio of FHA- and Prn-specific IgG2/IgG1 antibodies elicited by BcfA/FHA/Prn.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations